(untitled) (Communication & Society, 2019)
The personality of a political candidate, above and beyond governments and parties, is understood increasingly more as a brand image. The new political influencers are making a clean sweep of social networks and it is the media that reproduce an information model that, far from being grounded in transparency and quality, promotes a post-truth discourse, halfway between provocation and spectacle. This initial hypothesis focuses on Donald Trump’s profile, first as a presidential candidate and later on as US President. In parallel, Twitter users have swiftly succumbed to the leader’s appeal. Thus, this paper studies the impact of Trump’s tweets on the US reference press during the first 100 days of his presidency. More specifically, it analyses the correspondences between the tweets posted on his personal Twitter account (@realDonaldTrump, with more than 45 million followers) and the front page news in USA Today, The Boston Globe, The Wall Street Journal and The New York Times. Regarding public response, digital prosumer metrics (“likes,” retweets and comments) have been quantified in order to verify the degree of influence exerted by Trump on public opinion. The method employed here includes a quantitative and qualitative content analysis based on three categories: the politician’s tweets, front page news and online user metrics. The results confirm Trump’s empowerment on Twitter as both a main source of news and a political influencer as regards the media and the citizenry.